The Galileo affair : a documentary history - Finocchiaro, Maurice A., 1942-; Galilei, Galileo, 1564-1642; Galilei, Galileo, 1564-1642 (California studies in the history of science., 1989)
"A classic introduction to Galileo's masterpiece."--William A. Wallace, author of Galileo's Logic of Discovery and Proof."--